Riboflavin (vitamin B2) and oxidative stress: a review. Issue 11 (14th June 2014) - Ashoori, Marziyeh; Saedisomeolia, Ahmad
<x content-type="archive" xml:space="preserve">Abstract</x> Oxidative stress is involved in the development of many chronic diseases. One of the main factors involved in oxidative stress reduction is increased antioxidant potential. Some nutrients such as vitamin C, vitamin E and carotenoids are known to act as antioxidants; however, riboflavin is one of the neglected antioxidant nutrients that may have an antioxidant action independently or as a component of the glutathione redox cycle. Herein, studies that have examined the antioxidant properties of riboflavin and its effect on oxidative stress reduction are reviewed. The results of the reviewed studies confirm the antioxidant nature of riboflavin and indicate that this vitamin can protect the body against oxidative stress, especially lipid peroxidation and reperfusion oxidative injury. The mechanisms by which riboflavin protects the body against oxidative stress may be attributed to the glutathione redox cycle and also to other possible mechanisms such as the conversion of reduced riboflavin to the oxidised form.